PENGARUH CURRENT RATIO, RASIO LEVERAGE DAN ROI TERHADAP RISIKO SISTEMATIS SAHAM INDUSTRI MAKANAN DAN MINUMAN BURSA EFEK INDONESIA - Akhmad Sodikin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
This study aims to determine the effect of current ratio, leverage ratio and the ROI of the systematic risk of the food and beverage industry shares the Indonesia Stock Exchange simultaneously. This study is also to determine the effect on the current ratio partially systematic risk, leverage ratios determine the effect on the risk of systematic partially and to determine the effect of ROI on the risk of systematic food and beverage industry shares partially. To analyze the effect of the simultaneous use of multiple regression analysis with F test and to analyze the effect of partially then used simple regression with t test. The data in this analysis are taken as many as 14 food and beverage industry companies by the end of 2015. Based on data analysis showed that variables CR and debt ratio. The results showed that the variables CR, debt ratios and ROI no effect on beta stocks simultaneously. It can be seen calculated F value of 0.475 with a significance of 0.707. Variable CR, debt ratios and ROI affects beta sebear 12.5% ​​stake. CR variable does not affect the partial beta stocks. Thitung of -0.967 and significance of 0.352. These variables may explain the variable rate of 7.2% .Variabel debt ratio also does not affect the partial beta stocks. T value of 0.455 and siginifikansi amounted to 0.657. The variables affecting the stock beta of 1.7% while the rest influenced by other variables that are not included in the model. Variable ROI also does not affect the partial beta stocks. T value of -1.198 and siginifikansi at 0.254. The variables affecting the stock beta of 10.7% while the rest influenced by other variables that are not included in the model.